Fabrication of (Polymer Blend-magnesium Oxide) Nanoparticle and Studying their Optical Properties for Optoelectronic Applications - Alaa J. Kadham; Dalal Hassan; Najlaa Mohammad; Ahmed Hashim Ah-yasari (Bulletin of Electrical Engineering and Informatics, 2018)
Nanocomposites used in many optical devices applications. This aims to preparation of new type of polymer and study their optical properties. The polyvinyl pyrrolidone-carboxymethyl cellulose blend and magnesium oxide nanocomposites have been fabricated. The nanocomposites are prepared for different concentrations of polymer blend and magnesium oxide nanoparticles. The optical properties of nanocomposites were studied. The experimental results showed that the absorbance, absorption coefficient, refractive index, extinction coefficient, real and imaginary parts of dielectric constant and optical conductivity of (PVP-CMC) blend are increased with increase of the MgO nanoparticles concentration. The transmittance and energy band gap are decreased with increase of the MgO nanoparticles concentration. The nanocomposites have high absorbance in UV region which may be used for radiation shielding application.